Occupational hand dermatitis web survey in a university hospital during COVID-19 pandemic: the SHIELD study : The SHIELD study - Rizzi, Angela; Inchingolo, Riccardo; Viola, Marinella; Boldrini, Luca; Lenkowicz, Jacopo; Lohmeyer, Franziska Michaela; De Simone, Francesco Maria; Staiti, Domenico; Sarnari, Caterina; Gasbarrini, Antonio; Nucera, Eleonora (La Medicina del Lavoro, 2021)
Background: Occupational hand dermatitis (OHD) is a skin disease occurring on employees’ hands in certain jobs. Little is known about prevalence, incidence and characteristics of this adverse skin reaction and its associated risk factors during COVID-19 pandemic. To evaluate both prevalence and incidence of OHD and associated risk factors in Italian clinicians. Methods: A cross-sectional study was performed using a self-report questionnaire. Results: Two hundred and thirty clinicians responded to the survey and 82% of responders did not report previous OHD history before the COVID-19 pandemic. Daily use of gloves was reported by 80% of responders. OHD prevalence was 18%, while incidence was 80%. We found a protective effect on symptom occurrence for vinyl/nitrile gloves if the time with gloves was ≥ 6 hours per day. Conclusions: This survey reveals a high OHD incidence in an Italian population of clinicians. Furthermore, wearing vinyl/nitrile gloves for at least 6 hours a day had a protective effect on symptom onset.